Effects of foreign direct investment on the performance of local labour markets - The case of Hungary - Karoly Fazekas (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2003)
Post transitional labour markets of the CEE countries have been characterised by marked regional differences. Since labour market differences were mainly generated by demand side factors the paper will concentrate on the spatial pattern of job creation determined mostly by the allocation decisions of foreign investors. Thus, the success or failure of local economies or local labour markets were largely determined by the attractiveness of the individual regions towards FDI. Posttransitional winners of local labour markets can boast of high doses of FDI inflows, while high unemployment regions have been suffering a persistent lack of outside investments. Our analysis intends to identify the winners and losers of transitional local labour markets and to calculate the possible effects of EU-accession on local labour markets in Hungary. Based on micro regional data sets the paper describes the regional distribution of foreign and domestic employment. The first section of the paper discusses the time path of regional labour market differences in Hungary between 1990 - 2001 and identifies the winners and losers of transition. The second chapter analyses the spatial distribution of FDI and domestic firm's employment and identifies the most important explanatory factors of their regional distribution.
Keywords: F02; F23; J40; R12; 330; local labour markets; FDI; transition economies; Hungary